The Effect of Using WhatsApp Media Toward Students’ Reading Comprehension on Narrative Text At The Tenth Grade of SMAN 9 Mandau - Wahyu Muhammad Zul'Arif (Unit Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Agama Islam Hubbulwathan, Duri, Indonesia, 2024)
This study was conducted to determine The effect of using WhatsApp media toward students’ reading comprehension on narrative text at the tenth grade of SMAN 9 Mandau. Quantitative method with a quasi-experimental research design. The research population is all class X which totals 329 students consisting of 9 classes. Due to the large population, the researcher took a sample of 68 students. In this study, the average pre-test score of the experimental class was 65.64 and the control class was 54.73. Meanwhile, the experimental post-test class was 76.47 and the control class was 68.44. It can be concluded that there is a significant influence on the ability to read narrative text through WhatsApp media.